Residents’ participation in energy performance certification for collective action on climate change: the case of EnerGuide - Chen, Xinyu; Gou, Zhonghua; Zhang, Huihua (Frontiers in Psychology, 2023)
ABSTRACT: Although various governments have issued energy performance certification (EPC) programmes to increase residential energy efficiency, there is little research helping to understand residents’ perception and acceptance of these programmes. This study contextualizes residents’ intention to participate in EPC programmes in their attribution and attitude toward climate change, aiming to find intermediating factors and effects that can help trigger collective action on reducing energy demand in the residential sector. Using EnerGuide, a Canadian energy efficiency rating and labelling programme as the example, this study successfully established a framework to explain that local residents' internal and external attribution to climate change elicited their positive attitudes (need to take action), thereby increasing their recognition of benefits of energy efficiency programmes, which further promoted their acceptance of the EnerGuide programme and their participation intention. The study provides an example of using the discourse of climate change to motivate residents' participation in energy efficiency programmes.